2015
DOI: 10.3390/molecules200915976
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Preliminary Biological Evaluation of 1,3,5-Triazine Amino Acid Derivatives to Study Their MAO Inhibitors

Abstract: Three series of 4,6-dimethoxy-, 4,6-dipiperidino-and 4,6-dimorpholino-1,3,5-triazin-2-yl) amino acid derivatives were synthesized and characterized. A preliminary study for their monoamine oxidase inhibitory activity showed that compounds 7, 18, and 25 had MAO-A inhibition activity comparable to that of the standard clorgyline, with apparently more selective inhibitory activity toward MAO-A than MAO-B and no significant acute toxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…All solvents and reagents were purchased from Sigma–Aldrich. The 1,3,5‐triazinyl l ‐amino acid derivatives 1 a – g , 2 a , b , d , e , g and 3 a , b , d , e , g were prepared previously in our laboratory . Unless otherwise stated, normal workup from organic solvents involved drying over Na 2 SO 4 and rotary evaporation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All solvents and reagents were purchased from Sigma–Aldrich. The 1,3,5‐triazinyl l ‐amino acid derivatives 1 a – g , 2 a , b , d , e , g and 3 a , b , d , e , g were prepared previously in our laboratory . Unless otherwise stated, normal workup from organic solvents involved drying over Na 2 SO 4 and rotary evaporation.…”
Section: Methodsmentioning
confidence: 99%
“…The 1,3,5-triazinyl l-amino acid derivatives 1a-g, 2a,b,d,e,g and 3a,b,d,e,g were prepared previously in our laboratory. [38] Unless otherwise stated, normal workup from organic solvents involved drying over Na 2 SO 4 and rotary evaporation. TLC was performed General procedure for the synthesis of N-(4,6-dipiperidino-1,3, 5-triazin-2-yl) dipeptide ethyl esters (5 a,b,d,e,g):H ATU( 0.19 g, 0.5 mmol) was added to an ice-cold solution of the N a -(4,6-dipiperidino-1,3,5-triazin-2-yl)amino acid (0.5 mmol) and DIEA (0.17 mL, 1mmol) in DMF (2 mL) with stirring.…”
Section: Methodsmentioning
confidence: 99%
“…5 These compounds belong to the 1,3,5-triazine class of compounds, which are being exploited as anticancer and antimicrobial agents in their derivatized forms. 54,55 Upon analysing the chemical nature of the substrates, it was concluded that all the compounds which underwent deamination by Msd exhibit a typical azapyrimidine-like scaffold; isoguanine, a purine substrate of Msd, also displays similar conjugation chemistry to s-triazines (Fig. 6B).…”
Section: Structural and Functional Analyses Of Msdmentioning
confidence: 99%
“…[4,12,19,20]. Taking advantage of the unique reactivity shown by TCT, we have synthesized several s-triazine derivatives and evaluated their activity for several biological targets, which will be discussed in subsequent sections [13,14,[21][22][23][24][25][26][27][28]. TCT has been further explored as a linker that encompasses two key chemical concepts, namely orthogonality and chemoselectivity [8,16,29].…”
Section: Introductionmentioning
confidence: 99%